Ask Question
14 April, 07:03

Solve for d. Show each step for full credit. Circle your final answer. d (e - f) = g

+1
Answers (1)
  1. 14 April, 07:14
    0
    d (e - f) = g

    To solve for d, divide both sides by (e-f):

    d = g / (e-f)
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Solve for d. Show each step for full credit. Circle your final answer. d (e - f) = g ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers